Estilos parentales y el desarrollo socioafectivo en los adolescentes de la Unidad Educativa Nicolás Infante Díaz, año 2019 - Álvarez Delgado, Diana Elizabeth (2019)
During the first years of life, it is virtually impossible to separate emotional development and social development, as the two go hand in hand and are largely responsible for appropriate evolution in other areas of adolescent development. For this reason, a strong emotional basis allows adolescents to open theself to the physical and social world with security and confidence, acting as a facilitator of the proper cognitive and psychosocial evolution. Therefore, this research has as its main objective to determine the influence of parental styles on the socio-affective development of adolescents of the Educational Unit Nicolás Infante Díaz, year 2019. Because the family is the main context for the development of communication and the role model of parents' figures; The correct interdependence of family dynamics is a source of psychological, personal, educational, social and emotional well-being that will influence the adolescent. A qualitative methodology was applied, in which questionnaires were applied that resulted in the breeding styles predominant among adolescents in the educational unit "Nicolás Infante Díaz", it is concluded that parents exhibit a style Authorizer (verbal correction, physical correction, deprivation). These types of parents often have great self-control with their children, as well as between high demands and clear communication about what is expected of them. they also attach importance to autonomy and discipline. The parenting styles presented give way to socio-emotional problems among adolescents, as they often do not meet expectations, especially schoolchildren It was proposed to implement intervention strategies to promote styles allow for adequate socio-affective development in adolescents.